A method for modifying a self-assembled hole transport layer with alkali metal acetate
By using alkali metal acetate to modify the self-assembled hole transport layer in the hole transport layer of the perovskite solar cell, the problem of high cost and limited efficiency of the hole transport layer in the prior art is solved, and the photoelectric conversion efficiency of the perovskite solar cell is improved.
Patent Information
- Application Number
- CN202210049072.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-01-17
AI Technical Summary
The hole transport layer of existing perovskite solar cells has problems of high cost, limited efficiency and parasitic absorption, and traditional structures have few research on the charging transport layer modification of inverted batteries.
The self-assembled hole transport layer is modified by alkali metal acetate. The hole transport layer with a thickness of 1 to 300 nm is prepared by spin-coating an ethanol solution of SAMs material doped with alkali metal acetate on a transparent conductive substrate.
The adsorption rate of SAMs materials on the transparent conductive oxide substrate is improved, the optical response of the hole transport layer is improved, the extraction rate of holes is promoted, and the photoelectric conversion efficiency of perovskite solar cells is improved.
Smart Images

Figure CN114420853B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photovoltaics, and in particular relates to a method for modifying a self-assembled hole transport layer by alkali metal acetate. Background Art
[0002] In 1883, scientist Charles Fritts first produced solar cells that can directly convert solar energy into electrical energy. In the following century, scientists developed traditional photoelectric conversion materials such as silicon-based solar cells and compound solar cells. In 2009, Japanese scientist Miyasaka introduced the perovskite material MAPbI3 into solar cell devices. After nearly ten years of development, the efficiency of the cell has increased from the initial 3.8% to the current 25.5%, making perovskite solar cells a shining star of the new generation of solar cells due to their good photoelectric properties, high light absorption rate, simple preparation and large-area flexible preparation.
[0003] Early research on perovskite solar cells focused on improving the composition and quality of perovskite films, but as research progresses, more and more researchers are aware of the importance of charge transport layers in solar cells. For example, low energy conversion efficiency is caused by interface defects, energy level arrangement and charge distribution. In addition, the interface also affects the stability of the device due to ion diffusion, chemical reaction and degradation.
[0004] Although considerable progress has been made in the research on the hole transport layer of perovskite batteries, there are still some problems, mainly manifested as follows:
[0005] (1) Some commonly used hole transport layers are expensive and have limited efficiency.
[0006] (2) There is a certain amount of parasitic absorption.
[0007] At present, most of the related work on hole transport layer is focused on the traditional formal structure, and there are few reports on the modification of the charge transport layer of inverted cells. In recent years, SAMs self-assembled monolayer materials (carbazoles with phosphonic acid anchoring groups, such as MeO-2PACz, 2PACz, Me-4PACz, Br-2PACz, TPA, EADR04) have been applied to inverted solar cells due to their simple preparation, small parasitic absorption, low material consumption, and conformal coverage with the substrate, replacing the classic PTAA, NiO X However, this self-assembled material also has some disadvantages that cannot be ignored, such as being too thin, requiring an oxygen-containing bottom for adsorption, and adsorption inhomogeneity, which limits its further development. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for modifying a self-assembled hole transport layer with alkali metal acetate.
[0009] The method for modifying the self-assembled hole transport layer with alkali metal acetate comprises the following steps:
[0010] S1. Cleaning the transparent conductive substrate;
[0011] S2. Spin coating a precursor solution on a transparent conductive substrate at a set speed for a set time; the precursor solution is an ethanol solution of a SAMs material doped with alkali metal acetate, and then annealing at a set temperature for a set time; preparing a hole transport layer with a thickness of 1 to 300 nm with the introduced modification material on the transparent conductive substrate.
[0012] Preferably, in step S1, the transparent conductive substrate is ITO glass, FTO glass or a transparent metal electrode.
[0013] Preferably, in step S2, the alkali metal acetate is sodium acetate or potassium acetate; and the concentration of the precursor solution is 0.33-0.83 mg / mL.
[0014] Preferably, in step S2, the annealing temperature is 100° C., and the annealing time is 10 min; the rotation speed of spin coating the precursor solution is 4000 rpm, and the spin coating time of the precursor solution is 30 s.
[0015] The application of the method of modifying the self-assembled hole transport layer with alkali metal acetate in perovskite solar cells comprises the following steps:
[0016] S1. Cleaning the transparent conductive substrate;
[0017] S2, spin coating a precursor solution raw material on a transparent conductive substrate at a set speed for a set time; the precursor solution raw material is an ethanol solution of a SAMs material doped with an alkali metal acetate, and then annealing at a set temperature for a set time; preparing a hole transport layer with a thickness of 1 to 300 nm and introducing a modification material on the transparent conductive substrate;
[0018] S3, preparing a perovskite light absorption layer ABX3 (perovskite film) with a thickness of 50 to 1500 nm on the hole transport layer by spin coating; wherein A is a metal element or an organic group, B is a metal cation, and X is a halogen ion;
[0019] S4, using thermal evaporation method An electron transport layer with a thickness of 1 to 300 nm is prepared on the perovskite light absorption layer at a deposition rate of 1.0;
[0020] S5. Prepare an electrode layer on the electron transport layer using a thermal evaporation coating method to obtain an alkali metal acetate-modified perovskite solar cell.
[0021] Preferably, in step S3, A is CH3NH3 + / MA + (methylamine ion), HC(NH2)2 + / FA + (formamidinium ion) or Cs element; B is Sn2 + or Pb2 + ; X is 1 - Br - or Cl - .
[0022] Preferably, the electron transport layer in step S4 is a C60 / BCP composite electron transport layer, a PTAA electron transport layer or a PEDOT:PSS electron transport layer.
[0023] Preferably, in step S5, the material of the electrode layer is Al, Ag or Au.
[0024] Preferably, before using the thermal evaporation coating method in step S5, the vacuum degree of the chamber is less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled to control the thickness of the metal silver electrode to be 100-200nm.
[0025] The beneficial effects of the present invention are:
[0026] The present invention introduces alkali metal acetate to modify the SAMs hole transport layer. Through pH testing, it is found that SAMs are acidic, while alkali metal acetate is alkaline. Therefore, the addition of alkali metal acetate consumes H in the solution. + , which causes the ionization equilibrium of phosphonic acid to move toward the positive direction, prompting more phosphonic acid to be ionized, thereby increasing the adsorption rate of SAMs materials on transparent conductive oxide (TCO) substrates (such as Figure 1 As shown), the optical response of the hole transport layer (HTL) interface is improved, the hole extraction rate is promoted, and the crystal quality of the perovskite is improved, thereby increasing the photoelectric conversion efficiency of the photovoltaic cell under working conditions.
[0027] The modification method of the present invention is applicable to the following battery structure, in which a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal electrode are sequentially arranged on a transparent conductive substrate. The preparation method of the battery is to sequentially prepare a hole transport layer, a perovskite light absorption layer, an electron transport layer and a metal anode electrode on a cleaned transparent conductive glass (FTO, ITO or a transparent metal electrode); the modification method of the present invention is compatible with the preparation process of a perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the action of alkali metal acetate;
[0029] Figure 2 The short-circuit current-open-circuit voltage curves of unmodified and NaAc-modified perovskite solar cells;
[0030] Figure 3 Short-circuit current-open-circuit voltage curves of unmodified and KaAc-modified perovskite solar cells. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with embodiments. The description of the following embodiments is only used to help understand the present invention. It should be noted that for ordinary persons in the art, without departing from the principle of the present invention, the present invention can also be modified in some ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0032] Comparative Example:
[0033] (1) A self-assembled hole transport layer and a perovskite film (ABX3, where A is MA (methylamine), FA (formamidine), Cs and their combinations, B is Sn, Pb and their combinations, and X is I, Br or Cl and their combinations) are sequentially prepared on a conductive substrate of ITO (indium tin oxide), FTO (fluorine-doped tin oxide) or a transparent metal electrode.
[0034] (2) Prepare an electron transport layer (C60 / BCP, PTAA, PEDOT:PSS) on the perovskite light absorption layer.
[0035] (3) Prepare Ag electrode on the electron transport layer by thermal evaporation coating. Before evaporation, the vacuum degree of the cavity should be less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled so that the thickness of the metal silver electrode is 100-300nm. A complete perovskite solar cell can be obtained.
[0036] Embodiment 1:
[0037] (1) An ethanol solution of MeO-2PACz doped with sodium acetate (NaAc) was spin-coated on a conductive substrate of ITO (indium tin oxide), FTO (fluorine-doped tin oxide) or a transparent metal electrode at a rotation speed of 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. A perovskite light absorption layer (ABX3, wherein A is MA (methylamine), FA (formamidine), CS and combinations thereof, B is Sn, Pb and combinations thereof, and X is I, Br or Cl and combinations thereof) was then prepared on the hole transport layer by spin coating.
[0038] (2) The electron transport layer C60 / BCP was prepared by thermal evaporation. The evaporation rate was controlled at
[0039] (3) Prepare Ag electrode on the electron transport layer by thermal evaporation coating method. Before evaporation, the vacuum degree of the chamber should be less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled so that the thickness of the metal silver electrode is 100-200 nm. The alkali metal acetate modified perovskite solar cell (device performance such as Figure 2 and Table 1).
[0040] Table 1 Photovoltaic parameter table of short-circuit current-open-circuit voltage curves of devices made without modification and after NaAc modification
[0041]
[0042] Embodiment 2:
[0043] (1) An ethanol solution of MeO-2PACz doped with potassium acetate (KaAc) was spin-coated on a conductive substrate of ITO (indium tin oxide), FTO (fluorine-doped tin oxide) or a transparent metal electrode at a rotation speed of 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. A perovskite light absorption layer (ABX3, wherein A is MA (methylamine), FA (formamidine), CS and combinations thereof, B is Sn, Pb and combinations thereof, and X is I, Br or Cl and combinations thereof) was then prepared on the hole transport layer by spin coating.
[0044] (2) The electron transport layer C60 / BCP was prepared by thermal evaporation. The evaporation rate was controlled at
[0045] (3) Prepare Ag electrode on the electron transport layer by thermal evaporation coating method. Before evaporation, the vacuum degree of the chamber should be less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled so that the thickness of the metal silver electrode is 100-200 nm. The alkali metal acetate modified perovskite solar cell (device performance such as Figure 3 and Table 2).
[0046] Table 2 Photovoltaic parameter table of short-circuit current-open-circuit voltage curves of devices made without modification and after KaAc modification
[0047]
[0048] Embodiment 3:
[0049] (1) An ethanol solution of Me-4PACz doped with sodium acetate (NaAc) was spin-coated on a conductive substrate of ITO (indium tin oxide), FTO (fluorine-doped tin oxide) or a transparent metal electrode at a rotation speed of 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. A perovskite light absorption layer (ABX3, wherein A is MA (methylamine), FA (formamidine), CS and combinations thereof, B is Sn, Pb and combinations thereof, and X is I, Br or Cl and combinations thereof) was then prepared on the hole transport layer by spin coating.
[0050] (2) The electron transport layer C60 / BCP was prepared by thermal evaporation. The evaporation rate was controlled at
[0051] (3) Prepare Ag electrode on the electron transport layer by thermal evaporation coating method. Before evaporation, the vacuum degree of the chamber should be less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled so that the thickness of the metal silver electrode is 100-200 nm. Thus, an alkali metal acetate-modified perovskite solar cell can be obtained.
[0052] Embodiment 4:
[0053] (1) An ethanol solution of Me-4PACz doped with potassium acetate (KAc) was spin-coated on a conductive substrate of ITO (indium tin oxide), FTO (fluorine-doped tin oxide) or a transparent metal electrode at a rotation speed of 4000 rpm for 30 s, followed by annealing at 100 °C for 10 min. A perovskite light absorption layer (ABX3, wherein A is MA (methylamine), FA (formamidine), CS and combinations thereof, B is Sn, Pb and combinations thereof, and X is I, Br or Cl and combinations thereof) was then prepared on the hole transport layer by spin coating.
[0054] (2) The electron transport layer C60 / BCP was prepared by thermal evaporation. The evaporation rate was controlled at
[0055] (3) Prepare Ag electrode on the electron transport layer by thermal evaporation coating method. Before evaporation, the vacuum degree of the chamber should be less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled so that the thickness of the metal silver electrode is 100-200 nm. Thus, an alkali metal acetate-modified perovskite solar cell can be obtained.
Claims
1. A method for modifying a self-assembled hole transport layer with an alkali metal acetate, characterized in that: The following steps are involved: S1. Cleaning the transparent conductive substrate; S2, spin coating the precursor solution on the transparent conductive substrate at a set speed for a set time; The precursor solution is an ethanol solution of a SAMs material doped with an alkali metal acetate, wherein the SAMs material is a carbazole body having a phosphonic acid anchoring group, and then annealing is performed at a set temperature for a set time; A hole transport layer with a thickness of 1 to 300 nm and introduced with a modification material is prepared on a transparent conductive substrate.
2. The method for modifying a self-assembled hole transport layer with alkali metal acetate according to claim 1, characterized in that: In step S1, the transparent conductive substrate is ITO glass, FTO glass or a transparent metal electrode.
3. The method for modifying a self-assembled hole transport layer with alkali metal acetate according to claim 1, characterized in that: In step S2, the alkali metal acetate is sodium acetate or potassium acetate; and the concentration of the precursor solution is 0.33-0.83 mg / mL.
4. The method for modifying a self-assembled hole transport layer with alkali metal acetate according to claim 1, characterized in that: In step S2, the annealing temperature is 100° C., and the annealing time is 10 min; the rotation speed of spin coating the precursor solution is 4000 rpm, and the spin coating time of the precursor solution is 30 s.
5. An application of the method for modifying a self-assembled hole transport layer with alkali metal acetate as claimed in any one of claims 1 to 4 in a perovskite solar cell, characterized in that: The steps include: S1. Cleaning the transparent conductive substrate; S2, spin coating a precursor solution raw material on a transparent conductive substrate at a set speed for a set time; the precursor solution raw material is an ethanol solution of a SAMs material doped with an alkali metal acetate, and then annealing at a set temperature for a set time; preparing a hole transport layer with a thickness of 1 to 300 nm and introducing a modification material on the transparent conductive substrate; S3, preparing a perovskite light absorption layer ABX3 with a thickness of 50 to 1500 nm on the hole transport layer by spin coating; wherein A is a metal element or an organic group, B is a metal cation, and X is a halogen ion; S4, using thermal evaporation method An electron transport layer with a thickness of 1 to 300 nm is prepared on the perovskite light absorption layer at a deposition rate of 1.0; S5. Prepare an electrode layer on the electron transport layer using a thermal evaporation coating method to obtain an alkali metal acetate-modified perovskite solar cell.
6. Application of the method for modifying the self-assembled hole transport layer with alkali metal acetate according to claim 5 in perovskite solar cells, characterized in that: In step S3, A is CH3NH3 + / MA + 、HC(NH2)2 + / FA + or Cs element; B is Sn2 + or Pb2 + ; X is 1 - Br - or Cl - .
7. Application of the method for modifying the self-assembled hole transport layer with alkali metal acetate according to claim 5 in perovskite solar cells, characterized in that: In step S4, the electron transport layer is a C60 / BCP composite electron transport layer, a PTAA electron transport layer or a PEDOT:PSS electron transport layer.
8. Application of the method for modifying the self-assembled hole transport layer with alkali metal acetate according to claim 5 in perovskite solar cells, characterized in that: In step S5, the material of the electrode layer is Al, Ag or Au.
9. Application of the method for modifying the self-assembled hole transport layer with alkali metal acetate according to claim 5 in perovskite solar cells, characterized in that: Before using the thermal evaporation coating method in step S5, the vacuum degree of the chamber is less than 4×10 -6 Pa, by adjusting the current and voltage range of the power supply, the evaporation speed of the film is controlled within The evaporation time is controlled to control the thickness of the metal silver electrode to be 100-200nm.
Citation Information
Patent Citations
Perovskite planar heterojunction solar battery based on self-assembled monolayer
CN104465992A